2013
DOI: 10.3402/qhw.v8i0.21880
|View full text |Cite
|
Sign up to set email alerts
|

When expressions make impressions—Nurses’ narratives about meeting severely ill patients in home nursing care: A phenomenological-hermeneutic approach to understanding

Abstract: Registered nurses (RNs) working in homecare encounter severely ill and palliative patients whose expressions may cause ethical challenges and influence their daily work. The aim of this qualitative study was to illuminate and interpret the meaning of nurses’ lived experiences when meeting these patients. Narrative interviews were conducted with 10 RNs working in home nursing care. These interviews were audiotaped and transcribed verbatim to a text and interpreted by a phenomenological-hermeneutic method inspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…Other words for the nurses' role as being dedicated and present were to open oneself to the other . The study by Devik, Enmarker, and Hellzen () found that being dedicated meant being open to the presence of the other. To be open meant to experience the patients' lives, sensing their milieu and their history and context, and presupposes openness to the nurse's own existence and emotions.…”
Section: Resultsmentioning
confidence: 99%
“…Other words for the nurses' role as being dedicated and present were to open oneself to the other . The study by Devik, Enmarker, and Hellzen () found that being dedicated meant being open to the presence of the other. To be open meant to experience the patients' lives, sensing their milieu and their history and context, and presupposes openness to the nurse's own existence and emotions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, nurses' actions in HC involve reflective, not mechanistic, practice (35) . Thus, the need for reflection on the development of work in the home environment was identified (10,(14)(15)20,35) . Reflection is essential for recognizing weaknesses and/or limits in situations that demand resignification of work in home care.…”
Section: Necessary Knowledge For Nursing Practice In Home Carementioning
confidence: 99%
“…In the relationship with caregivers, nurses act as facilitators, encouraging them to express their worries and experiences with patient care while searching for physical, emotional, and mental comfort for patients and caregivers (48) . Moreover, in interpersonal relationships, nurses present themselves as open to others (10) and are considered capable of caring with love, compassion, and confidence, acting as "counselors" because they listen and welcome families with their worries and fears (11) .…”
Section: Nursing Actions In Home Carementioning
confidence: 99%
See 1 more Smart Citation
“…In that light, our findings address fundamental structures and values built into healthcare practices. According to Devik et al [38], there is a great need to focus attention on the emotional dimension and how it influences healthcare and not only to focus on knowledge-based analyses of situations.…”
Section: Discussionmentioning
confidence: 99%